Full scale demonstration of air-purifying pavement - Ballari, Maria de Los Milagros (2013)
Experiments concerning a full-scale demonstration of air purifying pavement in Hengelo, The Netherlands, are reported. The full width of the street was provided with concrete pavement containing TiO2 over a length of 150 m (“DeNOx street”). Another part of the street, about 100 m, was paved with normal paving blocks (“Control street”). The outdoor monitoring was done during 26 days for a period exceeding one year, and measured parameters included traffic intensity, NO, NO2 and ozone concentrations, temperature, relative humidity, wind speed and direction, and the visible and UV light irradiance. Prior and parallel to these field measurements, the used blocks were also measured in the lab to assess their performance. The NOx concentration was, on average, 19% (considering the whole day) and 28% (considering only afternoons) lower than the obtained values in the Control street. Under ideal weather conditions (high radiation and low relative humidity) a NOx concentration decrease of 45% could be observed.